Hybrid Passivated Red Organic LEDs with Prolonged Operation and Storage Lifetime - Dan-Dan Feng; Shuang-Qiao Sun; Wei He; Jun Wang; Xiao-Bo Shi; Man-Keung Fung (Molecules, 2022)
In addition to mobile and TV displays, there is a trend of organic LEDs being applied in niche markets, such as microdisplays, automobile taillights, and photobiomodulation therapy. These applications mostly do not require to be flexible in form but need to have long operation lifetimes and storage lifespans. Using traditional glass encapsulation may not be able to fulfill the rigorous product specification, and a hybrid encapsulation method by combining glass and thin-film encapsulation will be the solution. Conventional thin-film encapsulation technology generally involves organic and inorganic multilayer films that are thick and have considerable stress. As a result, when subjected to extreme heat and stress, the film easily peels off. Herein, the water vapor transmission rate (WVTR) of a 2 µm silicon nitride film prepared at 85 °C is less than 5 × 10−5 g/m2/day and its stress is optimized to be 23 MPa. Red organic LEDs are passivated with the hybrid encapsulation, and the T95 lifetime reaches nearly 10 years if the LED is continuously driven at an initial luminance of 1000 cd/m2. In addition, a storage lifespan of over 17 years is achieved.